Tinjauan Hukum Islam terhadap Praktik ODOL (Over Dimension Over Load) dalam Angkutan Barang di Indonesia: Analisis Maqashid Syari’ah dan Dampaknya terhadap Keselamatan Publik - ‘Arifin, Muhammad Tajul (Media Hukum Indonesia (MHI), 2025)
The practice of Over Dimension and Over Load (ODOL) in freight transportation in Indonesia represents a serious issue within the transportation sector, as it directly contributes to infrastructure damage and increases the risk of traffic accidents. Despite government efforts to regulate and mitigate ODOL practices through various policies and regulations, violations remain widespread. This study aims to examine ODOL practices from the perspective of Islamic law using the maqāṣid al-sharī‘ah approach, particularly concerning the protection of life (ḥifẓ al-nafs) and property (ḥifẓ al-māl), as well as the broader objective of maintaining public welfare (maṣlaḥah ‘āmmah). The research employs a qualitative method with a juridical–sharī‘ah approach. Data were collected through a literature review of classical and contemporary fiqh sources, statutory regulations, and relevant academic references. The findings reveal that ODOL practices contradict the principles of maqāṣid al-sharī‘ah as they entail harm (mafsadah), cause losses to others, and constitute a breach of social trust. Moreover, ODOL represents noncompliance with legitimate governmental regulations, which, according to Islamic teachings, must be obeyed as long as they do not conflict with the sharī‘ah. Therefore, from a normative Islamic legal perspective, ODOL practices are deemed impermissible as they violate the principles of justice, safety, and public welfare.